Manajemen Patien Safety dalam Meningkatkan Mutu Pelayanan Pasien - Budiman, Arif; Yudiansyah, Ridwan (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to analyze Patient Safety Management in Improving the Quality of Patient Services. The type of research is a literature review. Patient safety management has an important role in improving the quality of patient service. Implementation of patient safety principles, such as incident reporting, increasing staff competency, and implementing safety standards, has a significantly positive impact on health service quality indicators, including patient satisfaction, reducing the number of adverse medical events, and increasing operational efficiency. Challenges in implementing patient safety management, such as lack of resources and resistance to change, can be overcome through management commitment, ongoing training, and strengthening safety culture throughout the organization. Recommendations for further improvement include the development of stronger policies, increased staff participation in safety programs, and regular evaluation and adjustment of strategies to ensure the sustainability and effectiveness of patient safety programs.